Tumbling with a limp: local asymmetry in water's hydrogen bond network and its consequences - Elgabarty, Hossam; Kühne, Thomas (Physical Chemistry Chemical Physics)
Ab initio molecular dynamics simulations of ambient liquid water and energy decomposition analysis have recently shown that water molecules exhibit significant asymmetry between the strengths of the two donor and/or the two acceptor interactions.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Effects of KF and RbF treatments on Cu(In,Ga)Se2-based solar cells: A combined photoelectron spectroscopy and DFT study - Majumdar, I.; Sahoo, S.K.; Parvan, V.; Mirhosseini, Hossein; Chacko, B.; Wang, Y.; Greiner, D.; Kühne, Thomas; Schlatmann, R.; Lauermann, I. (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

C 2 N: A Class of Covalent Frameworks with Unique Properties - Tian, Zhihong; Lopez Salas, Nieves; Liu, Chuntai; Liu, Tianxi; Antonietti, Markus (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Key activity descriptors of nickel-iron oxygen evolution electrocatalysts in the presence of alkali metal cations - Görlin, Mikaela; Halldin Stenlid, Joakim; Koroidov, Sergey; Wang, Hsin-Yi; Börner, Mia; Shipilin, Mikhail; Kalinko, Aleksandr; Murzin, Vadim; Safonova, Olga V.; Nachtegaal, Maarten; Uheida, Abdusalam; Dutta, Joydeep; et al. (Nature Communications)
Abstract Efficient oxygen evolution reaction (OER) electrocatalysts are pivotal for sustainable fuel production, where the Ni-Fe oxyhydroxide (OOH) is among the most active catalysts for alkaline OER. Electrolyte alkali metal cations have been shown to modify the activity and reaction intermediates, however, the exact mechanism is at question due to unexplained deviations from the cation size trend. Our X-ray absorption spectroelectrochemical results show that bigger cations shift the Ni 2+/(3+δ)+ redox peak and OER activity to lower potentials (however, with typical discrepancies), following the order CsOH > NaOH ≈ KOH > RbOH > LiOH. Here, we find that the OER activity follows the variations in electrolyte pH rather than a specific cation, which accounts for differences both in basicity of the alkali hydroxides and other contributing anomalies. Our density functional theory-derived reactivity descriptors confirm that cations impose negligible effect on the Lewis acidity of Ni, Fe, and O lattice sites, thus strengthening the conclusions of an indirect pH effect.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Exploring the light-induced dynamics in solvated metallogrid complexes with femtosecond pulses across the electromagnetic spectrum - Naumova, Maria A.; Kalinko, Aleksandr; Wong, Joanne W. L.; Alvarez Gutierrez, Sol; Meng, Jie; Liang, Mingli; Abdellah, Mohamed; Geng, Huifang; Lin, Weihua; Kubicek, Katharina; Biednov, Mykola; Lima, Frederico; et al. (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Poling thin-film x-cut lithium niobate for quasi-phase matching with sub-micrometer periodicity - Zhao, Jie; Rüsing, Michael; Roeper, Matthias; Eng, Lukas M.; Mookherjea, Shayan (Journal of Applied Physics)
Quasi-phase-matched grating structures in lithium niobate waveguides with sub-micrometer periodicities will benefit the development of short-wavelength nonlinear optical devices. Here, we report on the reproducible formation of periodically poled domains in x-cut single-crystalline thin-film lithium niobate with periodicities as short as 600 nm. Shaped single-voltage poling pulses were applied to electrode structures that were fabricated by a combination of electron-beam and direct-writing laser lithography. Evidence of successful poling with good quality was obtained through second-harmonic microscopy and piezoresponse force microscopy imaging. For the sub-micrometer period structures, we observed patterns with a double periodicity formed by domain interactions and features with sizes <200 nm.
Keywords: General Physics and Astronomy

High Quality Entangled Photon Pair Generation in Periodically Poled Thin-Film Lithium Niobate Waveguides - Zhao, Jie; Ma, Chaoxuan; Rüsing, Michael; Mookherjea, Shayan (Physical Review Letters)
Keywords: General Physics and Astronomy

Calculating the distributions of number, mass and luminosity of the stars with the help of MS Excel - Hohmann, Sascha (European Journal of Physics)
Abstract Astrophysical topics can be treated with the methods of different areas of physics, mathematics and other natural sciences. The integration of these topics into such areas could improve students’ motivation and strengthen the connections between different fields of the mentioned sciences. In this article, an example of the connection between the physics of the stars and that of their statistical distributions is given. The usage of Microsoft Excel simplifies the mathematical requirements and gives the possibility of seeing the changes of distribution with the growing age of the regarded population of stars. The changes are a direct consequence to the limited lifetime of the stars and the limited age of the considered population of stars.
Keywords: General Physics and Astronomy

Azlactone-functionalized smart block copolymers for organocatalyst immobilization - Yu, Xiaoqian; Herberg, Artjom; Kuckling, Dirk (European Polymer Journal)
Keywords: Organic Chemistry; Polymers and Plastics; General Physics and Astronomy; Materials Chemistry

Experimental and numerical study of polyoxymethylene (Aldrich) combustion in counterflow - Glaznev, Roman K.; Karpov, Alexander I.; Korobeinichev, Oleg P.; Bolkisev, Andrei A.; Shaklein, Artem A.; Shmakov, Andrey G.; Paletsky, Alexander A.; Gonchikzhapov, Munko B.; Kumar, Amit (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Chemistry of iron nitrate-based precursor solutions for spray-flame synthesis - Stodt, Malte F. B.; Gonchikzhapov, Munko; Kasper, Tina; Fritsching, Udo; Kiefer, Johannes (Physical Chemistry Chemical Physics)
Understanding the chemistry of precursor solutions for spray-flame synthesis is a key step to developing inexpensive and large scale applications for tailored nanoparticles.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Estimating the Indistinguishability of Heralded Single Photons Using Second-Order Correlation - Faruque, Imad I.; Sinclair, Gary F.; Bonneau, Damien; Ono, Takafumi; Silberhorn, Christine; Thompson, Mark G.; Rarity, John G. (Physical Review Applied)
Keywords: General Physics and Astronomy

Second harmonic microscopy of poled x-cut thin film lithium niobate: Understanding the contrast mechanism - Rüsing, Michael; Zhao, J.; Mookherjea, S. (Journal of Applied Physics)
Thin film lithium niobate has been of great interest recently, and an understanding of periodically poled thin films is crucial for both fundamental physics and device developments. Second-harmonic (SH) microscopy allows for the noninvasive visualization and analysis of ferroelectric domain structures and walls. While the technique is well understood in bulk lithium niobate, SH microscopy in thin films is largely influenced by interfacial reflections and resonant enhancements, which depend on film thicknesses and substrate materials. We present a comprehensive analysis of SH microscopy in x-cut lithium niobate thin films, based on a full three-dimensional focus calculation and accounting for interface reflections. We show that the dominant signal in backreflection originates from a copropagating phase-matched process observed through reflections, rather than direct detection of the counterpropagating signal as in bulk samples. We simulate the SH signatures of domain structures by a simple model of the domain wall as an extensionless transition from a −χ(2) to a +χ(2) region. This allows us to explain the main observation of domain structures in the thin-film geometry, and, in particular, we show that the SH signal from thin poled films allows to unambiguously distinguish areas, which are completely or only partly inverted in depth.
Keywords: General Physics and Astronomy

Ergodic Rate for Fading Interference Channels with Proper and Improper Gaussian Signaling - Soleymani, Mohammad; Santamaria, Ignacio; Lameiro, Christian; Schreier, Peter J. (Entropy)
This paper studies the performance of improper Gaussian signaling (IGS) over a 2-user Rayleigh single-input single-output (SISO) interference channel, treating interference as noise. We assume that the receivers have perfect channel state information (CSI), while the transmitters have access to only statistical CSI. Under these assumptions, we consider a signaling scheme, which we refer to as proper/improper Gaussian signaling or PGS/IGS, where at most one user may employ IGS. For the Rayleigh fading channel model, we characterize the statistical distribution of the signal-to-interference-plus-noise ratio at each receiver and derive closed-form expressions for the ergodic rates. By adapting the powers, we characterize the Pareto boundary of the ergodic rate region for the 2-user fading IC. The ergodic transmission rates can be attained using fixed-rate codebooks and no optimization is involved. Our results show that, in the moderate and strong interference regimes, the proposed PGS/IGS scheme improves the performance with respect to the PGS scheme. Additionally, we numerically compute the ergodic rate region of the full IGS scheme when both users can employ IGS and their transmission parameters are optimized by an exhaustive search. Our results suggest that most of the Pareto optimal points for the 2-user fading IC channel are attained when either both users transmit PGS or when one transmits PGS and the other transmits maximally improper Gaussian signals and time sharing is allowed.
Keywords: General Physics and Astronomy

Quantum-Limited Time-Frequency Estimation through Mode-Selective Photon Measurement - Donohue, J. M.; Ansari, V.; Řeháček, J.; Hradil, Z.; Stoklasa, B.; Paúr, M.; Sánchez-Soto, L. L.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Liquid-liquid phase separation in dilute solutions of poly(styrene sulfonate) with multivalent cations: Phase diagrams, chain morphology, and impact of temperature - Hansch, Markus; Hämisch, Benjamin; Schweins, Ralf; Prévost, Sylvain; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Polyacrylates in the presence of an extraordinary monovalent cation—Solution behavior and metal nanoparticle formation - Urbanski, Anna; Hansch, Markus; Lopez, Carlos G.; Schweins, Ralf; Hertle, Yvonne; Hellweg, Thomas; Polzer, Frank; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Reaction enthalpy from the binding of multivalent cations to anionic polyelectrolytes in dilute solutions - Hansch, Markus; Kaub, Hans Peter; Deck, Sascha; Carl, Nico; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Structural heterogeneity in a parent ground-state structure of AnPixJg2 revealed by theory and spectroscopy - Scarbath-Evers, Laura Katharina; Jähnigen, Sascha; Elgabarty, Hossam; Song, Chen; Narikawa, Rei; Matysik, Jörg; Sebastiani, Daniel (Physical Chemistry Chemical Physics)
Extensive molecular dynamics simulations reveal two distinct isoforms of the cyanobacteriochrome AnPixJg2 (in its Pr state) with different chromophore conformations, yielding implications for spectroscopic properties.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

An experimental study of horizontal flame spread over PMMA surface in still air - Korobeinichev, Oleg; Gonchikzhapov, Munko; Tereshchenko, Alexander; Gerasimov, Ilya; Shmakov, Andrey; Paletsky, Alexander; Karpov, Alexander (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Reline aqueous solutions behaving as liquid mixtures of H-bonded co-solvents: microphase segregation and formation of co-continuous structures as indicated by Brillouin and 1H NMR spectroscopies - Posada, E.; Lopez Salas, Nieves; Jiménez Riobóo, R. J.; Ferrer, M. L.; Gutiérrez, M. C.; del Monte, F. (Physical Chemistry Chemical Physics)
Deep eutectic solvents (DESs) offer a suitable alternative to conventional solvents in terms of both performance and cost-effectiveness.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

High-Efficiency Plug-and-Play Source of Heralded Single Photons - Montaut, Nicola; Sansoni, Linda; Meyer-Scott, Evan; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)
Keywords: General Physics and Astronomy

Extracting the physical sector of quantum states - Mogilevtsev, D; Teo, Y S; Řeháček, J; Hradil, Z; Tiedau, J; Kruse, R; Harder, G; Silberhorn, Christine; Sanchez-Soto, L L (New Journal of Physics)
Keywords: General Physics and Astronomy

Talbot Effect for Exciton Polaritons - Gao, T.; Estrecho, E.; Li, G.; Egorov, O. A.; Ma, Xuekai; Winkler, K.; Kamp, M.; Schneider, C.; Höfling, S.; Truscott, A. G.; Ostrovskaya, E. A. (Physical Review Letters)
Keywords: General Physics and Astronomy

Blow-up of weak solutions to a chemotaxis system under influence of an external chemoattractant - Black, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Counterflow flames of ultrahigh-molecular-weight polyethylene with and without triphenylphosphate - Korobeinichev, O.P.; Gonchikzhapov, M.B.; Paletsky, A.A.; Tereshchenko, A.G.; Shundrina, I.K.; Kuibida, L.V.; Shmakov, A.G.; Hu, Y. (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Engineering the Frequency Spectrum of Bright Squeezed Vacuum via Group Velocity Dispersion in an SU(1,1) Interferometer - Lemieux, Samuel; Manceau, Mathieu; Sharapova, Polina; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Physical Review Letters)
Keywords: General Physics and Astronomy

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy

“On-the-fly” coupled cluster path-integral molecular dynamics: impact of nuclear quantum effects on the protonated water dimer - Spura, Thomas; Elgabarty, Hossam; Kühne, Thomas (Physical Chemistry Chemical Physics)
“On-the-fly” coupled cluster-based path-integral molecular dynamics simulations predict that the effective potential of the protonated water–dimer has a single-well only.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Giant narrowband twin-beam generation along the pump-energy propagation direction - Pérez, Angela M.; Spasibko, Kirill Yu; Sharapova, Polina; Tikhonova, Olga V.; Leuchs, Gerd; Chekhova, Maria V. (Nature Communications)
Abstract Walk-off effects, originating from the difference between the group and phase velocities, limit the efficiency of nonlinear optical interactions. While transverse walk-off can be eliminated by proper medium engineering, longitudinal walk-off is harder to avoid. In particular, ultrafast twin-beam generation via pulsed parametric down-conversion and four-wave mixing is only possible in short crystals or fibres. Here we show that in high-gain parametric down-conversion, one can overcome the destructive role of both effects and even turn them into useful tools for shaping the emission. In our experiment, one of the twin beams is emitted along the pump Poynting vector or its group velocity matches that of the pump. The result is markedly enhanced generation of both twin beams, with the simultaneous narrowing of angular and frequency spectrum. The effect will enable efficient generation of ultrafast twin photons and beams in cavities, waveguides and whispering-gallery mode resonators.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Liquid-nitrogen cooled, free-running single-photon sensitive detector at telecommunication wavelengths - Covi, M.; Pressl, B.; Günthner, T.; Laiho, K.; Krapick, Stefan; Silberhorn, Christine; Weihs, G. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

High-resolution X-ray absorption spectroscopy of iron carbonyl complexes - Atkins, Andrew J.; Bauer, Matthias; Jacob, Christoph R. (Physical Chemistry Chemical Physics)
We apply high-energy-resolution fluorescence-detected (HERFD) X-ray absorption near-edge structure (XANES) spectroscopy to study iron carbonyl complexes.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Covalency of hydrogen bonds in liquid water can be probed by proton nuclear magnetic resonance experiments - Elgabarty, Hossam; Khaliullin, Rustam Z.; Kühne, Thomas D. (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Phycocyanobilin in solution – a solvent triggered molecular switch - Watermann, Tobias; Elgabarty, Hossam; Sebastiani, Daniel (Phys. Chem. Chem. Phys.)
The chromophore phycocyanobilin changes its spectroscopic behaviour upon solvent change. Our calculations trace this effect back to conformational switching, induced by changes in the hydrogen bonding pattern.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Formation and interaction of resonance chains in the open three-disk system - Weich, Tobias; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)
Keywords: General Physics and Astronomy

A source of polarization-entangled photon pairs interfacing quantum memories with telecom photons - Clausen, C; Bussières, F; Tiranov, A; Herrmann, Harald; Silberhorn, Christine; Sohler, W; Afzelius, M; Gisin, N (New Journal of Physics)
Keywords: General Physics and Astronomy

Generation of Nonclassical Biphoton States through Cascaded Quantum Walks on a Nonlinear Chip - Solntsev, Alexander S.; Setzpfandt, Frank; Clark, Alex S.; Wu, Che Wen; Collins, Matthew J.; Xiong, Chunle; Schreiber, Andreas; Katzschmann, Fabian; Eilenberger, Falk; Schiek, Roland; Sohler, Wolfgang; Mitchell, Arnan; et al. (Physical Review X)
Keywords: General Physics and Astronomy

Tomography by Noise - Harder, G.; Mogilevtsev, D.; Korolkova, N.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Driven Quantum Walks - Hamilton, Craig S.; Kruse, Regina; Sansoni, Linda; Silberhorn, Christine; Jex, Igor (Physical Review Letters)
Keywords: General Physics and Astronomy

Interaction of a classical laser field with a model Rydberg atom in a mixed state prepared by entanglement with few-photon quantum light - Sharapova, Polina; Tikhonova, O V (Journal of Physics: Conference Series)
Keywords: General Physics and Astronomy

HERFD-XAS and valence-to-core-XES: new tools to push the limits in research with hard X-rays? - Bauer, Matthias (Phys. Chem. Chem. Phys.)
This perspective accounts for the benefits of the high resolution hard X-ray spectroscopic methods HERFD-XANES and valence-to-core-XES.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

First principles calculation of inhomogeneous broadening in solid-state cw-EPR spectroscopy - Elgabarty, Hossam; Wolff, Milian; Glaubitz, Adrian; Hinderberger, Dariush; Sebastiani, Daniel (Physical Chemistry Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Experimental Observation of the Spectral Gap in Microwave n-Disk Systems - Barkhofen, Sonja; Weich, Tobias; Potzuweit, A.; Stöckmann, H.-J.; Kuhl, U.; Zworski, M. (Physical Review Letters)
Keywords: General Physics and Astronomy

Hysteresis and memory factor of the Kerr effect in blue phases - Nordendorf, Gaby; Lorenz, Alexander; Hoischen, Andreas; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried; Wilkes, David; Wittek, Michael (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Hydrophobic gold nanoparticles via silane conjugation: chemically and thermally robust nanoparticles as dopants for nematic liquid crystals - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
We examine for the first time how chemically and thermally stable gold nanoparticles (NPs), prepared by a silane conjugation approach, affect both the thermal and the electro-optical properties of a nematic liquid crystal (LC), when doped at concentrations ranging from 0.25 to 7.5 wt%. We find that the octadecylsilane-conjugated gold NPs stabilize both the enantiotropic nematic and the monotropic smectic-A phases of the LC host with a maximum stabilization of 2 ° C for the nematic and 3.5 ° C for the smectic-A phases for the mixture containing 1 wt% of the silanized particles. The same mixture shows the lowest values for the Fréedericksz transition threshold voltage and the highest value for the dielectric anisotropy. Generally, all NP-containing mixtures, except mixtures with NP concentrations exceeding 5 wt%, reduce the threshold voltage, increase the dielectric anisotropy and reduce both rise and decay time; the latter particularly at temperatures at least 10 ° C below the isotropic–nematic phase transition on cooling.
Keywords: General Physics and Astronomy; General Engineering; General Mathematics

The chemical sensitivity of X-ray spectroscopy: high energy resolution XANES versus X-ray emission spectroscopy of substituted ferrocenes - Atkins, Andrew J.; Bauer, Matthias; Jacob, Christoph R. (Physical Chemistry Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef U.; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Silberhorn, Christine; Leuchs, Gerd; Marquardt, Christoph (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Spatio-spectral characteristics of parametric down-conversion in waveguide arrays - Kruse, R; Katzschmann, F; Christ, A; Schreiber, A; Wilhelm, S; Laiho, K; Gábris, A; Hamilton, C S; Jex, I; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy